Study of the effect of doping on the physical properties of pedot: PSS for applications as buffer layer in organic solar cell and as p-type material in thermoelectric device / Zurianti Abd. Rahman - Zurianti, Abd. Rahman (2015)
Poly (3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS) is the most common used hole transport layer material in organic electronic devices. Despite of several advantages of high transparency, stable work function, able to block electron and easy film formation, the low conductivity issue of PEDOT:PSS needs to be investigated. One of the feasible methods utilized in this study is the doping process of high boiling point polar solvent. Glycerol and ethylene glycol are the chosen polar solvents used to modify electrical properties of PEDOT:PSS. Another attempts to increase the conductivity of PEDOT:PSS, are by doping it with metal oxide of zinc oxide and aluminum zinc oxide. The optical, electrical and morphology properties of the doped PEDOT:PSS thin films are investigated. The modified PEDOT:PSS thin film is used as buffer layer in the fabrication of organic solar cell. The results obtained from the AFM images and Raman spectra show that the doped PEDOT:PSS thin films have experienced transformation in their polymer chain, lead in the variations of their optical and electrical properties. All doped PEDOT:PSS films exhibit more than 85% of transmissions, while the absorbance coefficient and energy gap Eg are enhanced accordingly. The sheet resistance of the doped films has been reduced drastically, thus the conductivity are increased gradually upon zinc oxide amount in PEDOT:PSS; where the conductivity has increased approximately to one order of magnitude (3.6 x 10-6 S/cm) as to compared to the pristine PEDOT:PSS (4.14 x 10 -7 S/cm). By introducing doped PEDOT:PSS as buffer layer in the standard organic solar cell (containing poly(3-hexylthiophene) P3HT and fullerene derivative, PCBM), the device efficiency has improved to some extend compared to the device utilizing the pristine PEDOT:PSS. The device with an amount of 4% ZnO doped PEDOT:PSS, exhibits the highest efficiency which increased about one magnitude factor from 0.0053% to 0.036%. The study is extended in observation of the thermal behavior of the doped PEDOT:PSS thin films with respect to the I-V behavior in order to seek their potential application in thermoelectric device. Further works in the fabrication of thermoelectric devices, are continued by combining a highly conductive PEDOT:PSS PH1000 as p-type material and organic n-type materials of PTCDA and Alq3. The I-V plots of all doped PEDOT:PSS with respect to variant in temperature difference are obtained based on the concept of thermoelectric device. The results indicate that the I-V behavior of pristine and only several doped PEDOT:PSS (2%, 4% of glycerol-doped and 4%, 6% EG-doped), have been affected by the changes in temperature gradient across the films. The encouraging results is obtained in the output power, Po, relative Seebeck coefficient, , internal electrical resistance, RD and efficiency factor,  of thermoelectric devices of PTCDA and Alq3 as n-type materials. The performance of these parameters indicate that both selected PEDOT:PSS/PTCDA or PEDOT/Alq3 can be utilized in thermoelectric device with further optimization. Overall, the modification of PEDOT:PSS with the selected polar solvent and metal oxide, can enhance the electrical properties of PEDOT:PSS to be utilized in organic solar cells or thermoelectric devices.